Ardra profiles of bacteria and archaea in mangrove sediments with different levels of contamination in the estuarine complex of Paranaguá, Brazil - Ribeiro,Catherine Gérikas (2013)
The mangrove's sediments from the coastal areas under human activities may contain significant contaminations by hydrocarbons, even when there are no visual evidences of it. The microorganisms are essential to these ecosystems, especially in the control of their chemical environment. Sediment samples were collected in two regions under different environment conditions (pristine and contaminated) of the Paranaguá Estuarine Complex (Paranaguá Bay and Laranjeiras Bay), Brazil. Aliphatic hydrocarbons were determined by the GC-FID to assess the status of contamination of the studied areas. The total DNA was extracted from these samples. The 16S rRNA gene was amplified by the PCR reactions with the pair of primers 21F and 958R for the archaeal domain, and 27F and 1492R for the bacterial domain. Comparisons of communities were made by the ARDRA technique, using the HinfI restriction enzyme. The phosphate concentration showed significant differences between the two regions. The aliphatic hydrocarbons analysis showed the presence of unresolved complex mixture (UCM), an indicator of oil contamination, in the samples from the Paranaguá Bay, which was corroborated by the concentration of total aliphatic hydrocarbons. The ARDRA profile indicated that the structure of archaeal and bacterial communities of the sampled areas was very similar. Therefore, the anthropogenic influences in the Paranaguá Bay showed to be not sufficient to produce disturbances in the prokaryotic dominant groups.